Significance of Basal ganglia calcification in Down's syndrome. Issue 3 (13th May 2020) - Thoms, Lesley; Idowu, Adelola; Nehra, Arjun; Biswas, Asit
Abstract : Purpose: There is high incidence of dementia in individuals with Down's syndrome. Much of the emphasis has been on Alzheimer's disease as being most prevalent; however, it is apparent that other dementia types are also likely, to which this patient cohort may be predisposed. Specifically, this paper aims to highlight the potential for subcortical dementias in Down's syndrome, suggesting a role for broader cognitive screening in aging individuals. Design/methodology/approach: This paper describes a case of a female with Down's syndrome and mild intellectual disability who presented with early signs of distinctive cognitive impairment and radiological calcification of the basal ganglia. Findings: An active 42-year-old lady, who was mostly independent of activities of daily living and in part-time employment, presented with a three-year history of progressive cognitive deficit, characteristic of subcortical decline. She had no personal or known family history of mental illness, epilepsy or dementia. Routine blood tests showed chronic renal impairment, mild hypocalcaemia and vitamin D deficiency, managed by her GP. CT scan showed only bilateral basal ganglia calcification. Originality/value: There is a widespread appreciation for the link between Down's syndrome and Alzheimer's disease but lesser consideration of the possibility of subcortical dementias. Given the differential nature and presentation of the two dementias, this case report highlights a need for clinicians to consider both to effectively manage these patients in the longer-term. Screening is discussed as a potential means of achieving this.